ANALISIS DAN PEMETAAN PRODUK UNGGULAN DAERAH KABUPATEN JEPARA SEBAGAI UPAYA PENINGKATAN PEREKONOMIAN DAERAH BERBASIS EKONOMI LOKAL - Noor Nailie Azzat; Febri Nugroho Mujiraharjo (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2020)
In the economic growth of an area external factors are able to have a large impact on the economy of a region but this growth is not able to survive because when this factor shifts it will also affect the economy, so one of the economic resilience of a region is through the development of a local economy based in the community economy. If seen from the structure forming the GRDP of Jepara Regency, Jepara Regency is an area with rural characteristics (Rural) which leads to the direction of an urban (Urban) characteristic where the economy is sustained by the agricultural sector for rural characteristics but in Jepara district it also grows rapidly its cultivation and growing large and retail trade. With this condition, Jepara Regency has great potential to develop Regional Superior Products (PUD), either later in the form of clusters or OVOP (one village one product).